2008
DOI: 10.1021/cm8010265
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly, Molecular Packing, and Electron Transport in n-Type Polymer Semiconductor Nanobelts

Abstract: We have found that poly(benzobisimidazobenzophenanthroline) (BBL) nanobelts can be prepared by a simple high-yield, solution-phase process, which enables dispersions of the nanobelts in a large number of solvents including environmentally benign solvents such as methanol and water. Characterization of the nanobelts by transmission electron and atomic force microscopies, electron diffraction, and X-ray diffraction showed that the BBL polymer chains are oriented parallel to the long axis of each nanobelt. This u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
140
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 68 publications
(64 reference statements)
8
140
0
Order By: Relevance
“…These unique materials combine the high-performance of singlecrystalline structures with solution-processability by dispersion (17,18). Several p-channel (hole-transporting) organic wires prepared by solution-processing have exhibited Ͼ 0.1 cm 2 /Vs for singlewire transistors (19)(20)(21)(22), whereas only a few solution-synthesized n-channel organic wires have been reported, typically with low performance ( Ϸ10 Ϫ3 Ϫ 10 Ϫ2 cm 2 /Vs) (23,24).Despite the intrinsic high mobility of single-crystalline wires, precise wire placement and wire-to-wire performance variation, due to the difference in the contact quality at the wire/insulator and wire/electrode interfaces, substantially hinder successful device integration (10, 25). Therefore, the technology to achieve network films of organic MWs deposited from a dispersion with controlled alignment and density is acutely desired.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These unique materials combine the high-performance of singlecrystalline structures with solution-processability by dispersion (17,18). Several p-channel (hole-transporting) organic wires prepared by solution-processing have exhibited Ͼ 0.1 cm 2 /Vs for singlewire transistors (19)(20)(21)(22), whereas only a few solution-synthesized n-channel organic wires have been reported, typically with low performance ( Ϸ10 Ϫ3 Ϫ 10 Ϫ2 cm 2 /Vs) (23,24).Despite the intrinsic high mobility of single-crystalline wires, precise wire placement and wire-to-wire performance variation, due to the difference in the contact quality at the wire/insulator and wire/electrode interfaces, substantially hinder successful device integration (10, 25). Therefore, the technology to achieve network films of organic MWs deposited from a dispersion with controlled alignment and density is acutely desired.…”
mentioning
confidence: 99%
“…These unique materials combine the high-performance of singlecrystalline structures with solution-processability by dispersion (17,18). Several p-channel (hole-transporting) organic wires prepared by solution-processing have exhibited Ͼ 0.1 cm 2 /Vs for singlewire transistors (19)(20)(21)(22), whereas only a few solution-synthesized n-channel organic wires have been reported, typically with low performance ( Ϸ10 Ϫ3 Ϫ 10 Ϫ2 cm 2 /Vs) (23,24).…”
mentioning
confidence: 99%
“…We conclude that the crystals of form D grew along the a axis, which coincides with the π-π stacking direction. [23,24] Adv. Electron.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the material, and growth conditions, some variations on the NW morphology have also been observed, e.g. flat 'nanobelts' [12] or curved 'nanofibres' [13]. We will here refer to all of these related morphologies as 'nanowires' as generic term, except when discussing a specific sample.…”
Section: Introductionmentioning
confidence: 99%
“…As n type organic semiconductor, we have selected poly(benzimidazobenzophenanthroline) (BBL). BBL can act as n type material in organic TFTs with good mobility ( e = 0.1 cm 2 /Vs) [20], and Briseno et al [12] have reported on the growth of BBL 'nanobelts'. BBL possesses a rather deep 'lowest unoccupied molecular orbital' (LUMO) of 4.0 eV [21], which allows reasonable electron injection even from high work function metals, and may make BBL consistent with water gating, despite the potential trapping of electrons by water and/or oxygen: Nicolai et al [22] recently suggested from theoretical calculations that such trapping can be avoided when the LUMO is more than 3.6 eV below vacuum level.…”
Section: Introductionmentioning
confidence: 99%